Knowledge modelling using the UML profile - Abdullah, Mohd Syazwan; Paige, Richard; Benest, Ian; Kimble, Chris (Springer US, 2006)
This paper discusses platform independent conceptual modeling of a knowledge intensive application, focusing on the use of knowledge-based systems (KBS) in the context of model-driven engineering. An extension to the Unified Modeling Language (UML) for knowledge modeling is presented based on the profiling extension mechanism of UML.The UML profile discussed in this paper has been successfully captured in a Meta-Object-Facility (MOF) based UML tool — the executable Modeling Framework (XMF).The example is that of modeling a knowledge-based system for the Ulcer Clinical Practical Guidelines (CPG) Recommendations.It demonstrates the use of the profile, with the prototype system implemented in the Java Expert System Shell (JESS).